Expression of cellular prion protein on platelets from patients with gray platelet or Hermansky-Pudlak syndrome and the protein's association with alpha-granules - Holada, Karel; Glierová, Hana; Šimák, Jan; Vostal, Jaroslav G (Haematologica, 2006)
The cellular prion protein (PrPc) is a membrane glycoprotein expressed on many human cells including platelets. We investigated the cellular localization of platelet PrPc. In resting platelets most PrPc was localized inside the cells. The correlation of PrPc and P-selectin surface up-regulation after platelet activation suggested its association with alpha-granules. This was confirmed by normal expression of PrPc on Hermansky-Pudlak syndrome platelets, which lack dense granules, and failure of gray platelet syndrome platelets, which lack alpha-granules, to up-regulate PrPc. Our results warrant further studies on the role of platelet PrPc in the transmission of prion diseases by blood transfusion.
Keywords: Blood Platelets; Hermanski-Pudlak Syndrome; trombocyty; PrPC Proteins; potransfuzní reakce; Humans; Heřmanského-Pudlákův syndrom; Prions; lidé; Transfusion Reaction; priony; Blood Transfusion; Creutzfeldt-Jakob Syndrome; Cytoplasmic Granules; PrPC proteiny; cytoplazmatická granula; krevní transfuze; Creutzfeldtova-Jakobova nemoc